Clinical Outcome of Open Reduction and Internal Fixation of Mandibular Condyle Fracture: A Prospective Observational Study - Shah, Arun Kumar; Gautam, Shailesh; Chaurasia, Nitesh; Yadav, Santosh Kumar (Journal of Karnali Academy of Health Sciences, 2024)
Introduction: Condyle of mandible plays crucial role in functioning of jaw. Untimely and inadequate treatment leads to deformity of face along with range of complications. The purpose of this study was to assess outcomes of open reduction and internal fixation of mandibular condyle fractures in terms of mouth opening, facial nerve function and occlusion.Methods: This was a prospective observational study conducted at Chitwan Medical College. Thirty-two patients of mandibular condyle fracture were treated by open reduction and internal fixation via retromandibular approach and evaluated for mouth opening, facial nerve function, and occlusion on 2nd day, 10th day and 25th day postoperatively. All collected data were entered on SPSS version 21 and analyzed using descriptive statistical methods. The results were presented as graphs and tables.Results: Of 32 patients, 7 patients show abnormal occlusion while 25 patients show normal occlusion. A gradual improvement in mouth opening and facial nerve function was also seen on 25th day.Conclusion: Open reduction and internal fixation gives superior clinical outcomes in terms of mouth opening, facial nerve function and occlusion. It also allows good anatomical repositioning and early function.